Sex hormones and risk of epilepsy: A bidirectional Mendelian randomization study - Ke, Bin; Li, Chunyu; Shang, Huifang (Frontiers in Molecular Neuroscience, 2023)
Background: Multiple evidence has suggested complex interaction between sex hormones and epilepsy. However, whether there exists a causal association and the effect direction remains controversial. Here we aimed to examine the causative role of hormones in the risk of epilepsy and vice versa. Methods: We conducted a bidirectional two-sample Mendelian randomization analysis using summary statistics from genome-wide association studies of major sex hormones including testosterone (N=425,097), estradiol (N=311,675) and progesterone (N=2,619), together with epilepsy (N=44,889). We further performed sex-stratified analysis, and verified the significant results using summary statistics from another study on estradiol in males (N=206,927). Results: Genetically determined higher estradiol was associated with a reduced risk of epilepsy (OR:0.90, 95% CI:0.83-0.98, P=9.51E-03). In the sex-stratified analysis, the protective effect was detected in males (OR:0.92, 95% CI:0.88-0.97, P=9.18E-04), but not in females. Such association was further verified in the replication stage (OR:0.44, 95% CI:0.23-0.87, P=0.017). In contrast, no association was identified between testosterone, progesterone and the risk of epilepsy. In the opposite direction, epilepsy was not causally associated with sex hormones. Conclusion: These results demonstrated higher estradiol could reduce the risk of epilepsy, especially in males. Future development of preventive or therapeutic interventions in clinical trials could attach importance to this.